2016
DOI: 10.1111/odi.12401
|View full text |Cite
|
Sign up to set email alerts
|

Human lactoferrin protects against Streptococcus mutans‐induced caries in mice

Abstract: These results show that endogenous LF protects against S. mutans-induced caries and that exogenous hLF can exert a protective effect against caries development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…125 In an in vitro study, the killing of S. mutans by human LF is dose-dependent. 126 These studies suggest that LF protects against S. mutans colonization and can therefore be used in dental caries prevention. Another study, focusing on children ( n =42, age range from 36 to 71 months), reported that the concentration of LF was higher in caries-free individuals than in ECC individuals.…”
Section: Salivary Proteins As a Protective Factor For Eccmentioning
confidence: 92%
“…125 In an in vitro study, the killing of S. mutans by human LF is dose-dependent. 126 These studies suggest that LF protects against S. mutans colonization and can therefore be used in dental caries prevention. Another study, focusing on children ( n =42, age range from 36 to 71 months), reported that the concentration of LF was higher in caries-free individuals than in ECC individuals.…”
Section: Salivary Proteins As a Protective Factor For Eccmentioning
confidence: 92%
“…The time allotted for the experiment was 42 days, as in previous studies [ 42 , 43 , 44 ], and the lesions developed within 5–7 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Lactoferrin is a highly cationic molecule that shows antimicrobial activity, in part, by binding and sequestering iron from pathogenic microorganisms 83 . Lactoferrin contributes to host defence in a non-redundant manner, as lactoferrin-deficient mice have increased susceptibility to Streptococcus mutans-induced dental caries, for example 84 .…”
Section: Wwwnaturecom/nrimentioning
confidence: 99%